2020
DOI: 10.21203/rs.3.rs-92741/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biochemical and Cellular Biomarkers in Brown Trout (Salmo trutta f. fario) in Response to the Antidepressants Citalopram and Venlafaxine

Abstract: Background: During the last decades, a worldwide increase in the number of cases of depression accompanied by rising prescription rates of antidepressants was recorded. In Germany, the two most prescribed antidepressants are the selective serotonin reuptake inhibitor (SSRI) citalopram and the serotonin and noradrenalin reuptake inhibitor (SNRI) venlafaxine, taking about 30 % of the market share. Both antidepressants are found frequently in surface waters and have the potential of adversely affecting aquatic or… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In addition, some studies showed that venlafaxine can lead to the formation of reactive oxygen species (ROS) causing cellular damage (Ahmadian et al, 2016; Zafir et al, 2009). Nevertheless, only a few studies have reported biochemical changes in fish (Ziegler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies showed that venlafaxine can lead to the formation of reactive oxygen species (ROS) causing cellular damage (Ahmadian et al, 2016; Zafir et al, 2009). Nevertheless, only a few studies have reported biochemical changes in fish (Ziegler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%